al-Bayhaqi wa-mawqifuhu min al-Ilahiyat - al-Ghamidi, Ahmad ibn'Atiyah ([al-Riyad] : al-Mamlakah al-'Arabiyah al-Sa'udiyah, Wizarah al-Ta'lim al-'Ali, Jami'ah al-Imam Muhammad ibn Sa'ud al-Islamiyah, Imadah al-Bahath al-Ilmi, 2002)
God; Islam; Views on God by al-Bayhaqi
Originally presented as the author's dissertation (doctoral)-- Jamiat al-Malik Abd al-Aziz, Mecca
Keywords: al-Bayhaqi, Ahmad ibn Husayn, -- 994-1066 -- Views on God; God (Islam); Islam -- Doctrines